Membangun Sistem Pengendalian Internal untuk Menanggulangi Resiko Fraud di Perusahaan - Jennie Aurellia Zaneta (Majelis: Jurnal Hukum Indonesia, 2024)
This article discusses the development of an internal control system as an effort to overcome the risk of fraud in the company. Through in-depth analysis of existing policies, procedures and practices, this research identifies key elements that can strengthen organizational integrity. Using a case study approach, this article shows how implementing effective controls, employee training, and reporting mechanisms can increase transparency and accountability. The results of this research conclude that a comprehensive internal control system not only reduces the risk of corruption, but also encourages an ethical culture in the work environment, thereby supporting the company's sustainability and reputation.